Two-step homogenization of textile composites using mechanics of structure genome. (1st July 2017) - Liu, Xin; Rouf, Khizar; Peng, Bo; Yu, Wenbin
Abstract: Mechanics of structure genome is extended to provide a novel two-step homogenization approach to predicting the effective properties of textile composites. The first homogenization step (micro-homogenization) deals with determining the effective properties of tows (yarns) from fiber and matrix properties. In the second homogenization step (macro-homogenization), the effective properties of textile composites are computed from the yarn and matrix properties. MSG is enabled to capture pointwise anisotropy that is due to woven microstructures. The finite thickness effects and inter-ply shift effects of textile composites are also accurately predicted by enabling MSG to treat aperiodic conditions in the thickness direction. A new software TexGen4SC, freely accessible in the cloud as an App athttps://cdmhub.org/resources/texgen4sc, is developed based on TexGen and MSG companion code SwiftComp™. TexGen4SC provides a fast and convenient way to compute properties of textile composites. Several numerical examples are presented to investigate the efficiency and accuracy of the proposed method.